Changes in the Risk of Sexual Reoffending: The Role and Relevance of Perceived Self-Efficacy and Adult Attachment Styles in Correctional Treatment. (December 2022) - Stück, Elisabeth; Briken, Peer; Brunner, Franziska
According to the Risk-Need-Responsivity (RNR) model, treatment effectiveness increases when treatment addresses all three associated core principles. While researchers have focused on the risk and need principles, responsivity remains under-investigated. The theoretical foundation of the RNR model and former research indicates low perceived self-efficacy and inadequate adult attachment styles as potential responsivity factors that can impede treatment of the underlying risk factors. This study assesses firstly whether these factors predict treatment attrition, and secondly changes in the assessed risk of sexual reoffending. Participants were N = 146 men sentenced for sexual offenses in a German social-therapeutic correctional facility. Younger age, higher number of previous convictions, and higher scores on the interpersonal facet of the Psychopathy Checklist-Revised are associated with a higher risk of treatment attrition. Unemployment prior to incarceration was found to be an aggravating factor, whereas substance abuse emerged as a mitigating factor, according reducing the risk of reoffending. Neither pre-treatment self-efficacy nor attachment styles revealed as responsivity factors in this study. Future studies should examine if the consideration of these factors during treatment might impact treatment outcomes.